Tuning the Swelling Behavior of Superabsorbent Hydrogels with a Branched Poly(aspartic acid) Crosslinker - Sunggyu Shin; Sangjin Kim; Sukhyeon Hong; Namhyun Kim; Juhwan Kang; Jaehyun Jeong (Gels)
Superabsorbent hydrogels used in products like diapers, hygiene items, and medical patches depend on their swelling ratio. However, improving the swelling performance across hydrogel assemblies remains challenging. This study identifies a decline in the water absorption capacity in hydrogel assemblies with high swelling ratios, as confirmed through MRI analysis, and introduces a solution using a branched crosslinker to address this issue. The branched crosslinker was synthesized by grafting acrylate groups onto poly(aspartic acid)s. This branched poly(aspartic acid) crosslinker was incorporated into hydrogels with the same number of acrylate groups as PEGDA575, a conventional linear crosslinker, and their absorption performance and behavior were compared. The results showed that hydrogels with the branched crosslinker exhibited a swelling ratio twice as high as the PEGDA575 group, with a slower initial absorption rate, demonstrating a more gradual swelling behavior. Additionally, while the initial absorption rate was approximately 30% slower than the PEGDA575 group, the absorption rate showed a gradual decrease of less than 15% within the first 30 min, indicating sustained absorption behavior. Overall, the new strategy presented in this study of introducing a branched crosslinker into hydrogels is expected to be a useful application for existing industries by enhancing swelling ratios and promoting continuous absorption.